2003
DOI: 10.1128/ec.2.2.295-305.2003
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Silencing of an Amoebapore Gene inEntamoeba histolytica: Molecular Analysis and Effect on Pathogenicity

Abstract: Transcriptional silencing of the gene coding for amoebapore A (AP-A) was observed when trophozoites of Entamoeba histolytica were transfected with a hybrid plasmid construct containing the ap-a gene flanked by the upstream and downstream segments of the original Ehap-a gene. Transfectants were totally devoid of ap-a transcript and AP-A protein. An identical silencing effect was observed upon transfection with a plasmid that contained only the 5 upstream region of ap-a. Removal of the selecting antibiotic enabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
158
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(165 citation statements)
references
References 54 publications
6
158
1
Order By: Relevance
“…Transcriptional gene silencing has been previously documented in E. histolytica. Bracha et al (11) showed that upon transfection with a plasmid containing the amoebapore gene and a portion of the short interspersed nuclear element EhSINE1, both chromosomal and episomal copies of the amoebapore gene were permanently silenced, and this silencing was stable even after removal of the plasmid (2). This permanent and stable epigenetic silencing mechanism is not completely understood, and whether a similar mechanism is functional in E. histolytica Rahman is not currently known.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transcriptional gene silencing has been previously documented in E. histolytica. Bracha et al (11) showed that upon transfection with a plasmid containing the amoebapore gene and a portion of the short interspersed nuclear element EhSINE1, both chromosomal and episomal copies of the amoebapore gene were permanently silenced, and this silencing was stable even after removal of the plasmid (2). This permanent and stable epigenetic silencing mechanism is not completely understood, and whether a similar mechanism is functional in E. histolytica Rahman is not currently known.…”
Section: Resultsmentioning
confidence: 99%
“…The cytotoxicity data are a significant finding, as the relative difficulty in manipulating gene expression in E. histolytica has limited the ability to associate particular genes with pathogenicity. To date, only a few amebic genes have been genetically shown to be involved in cytotoxicity (3,11,16,25,29,43,47).…”
Section: Macfarlane and Singh Eukaryot Cellmentioning
confidence: 99%
“…The protozoon discharges its effector proteins in the acidic environment of phagolysosomes in which engulfed bacteria are situated (40). Persuasive support for the involvement of amoebapores in extracellular killing of host cells comes from the finding that amoebapores are cytolytic toward eukaryotic cells (41,42) and that amoebae lacking the major form amoebapore A are no longer capable of killing mammalian cells or destroying host tissues in vitro (7). For the scenario of the cytolytic reaction, it may be envisaged that after amoeba-target cell contact has been established, amoebapores are discharged from cytoplasmic granules into the confined environment of the contact zone in which a high protein concentration and a relatively low pH may be reached.…”
Section: Resultsmentioning
confidence: 99%
“…They are capable of lysing a broad spectrum of target cells, including human host cells and bacteria. It has been recently shown that trophozoites of E. histolytica lacking amoebapore A, due to transcriptional silencing of the encoding gene, became avirulent (7), demonstrating that this protein is a key pathogenicity factor of the parasite. All three amoebapore isoforms have been isolated and biochemically characterized, and their primary structure has been elucidated by molecular cloning of the genes of their precursors (8 -10).…”
mentioning
confidence: 99%
“…The resulting disturbance of the endothelial barrier likely facilitates passage of trophozoites from the blood circulation into the hepatic tissue. E. histolytica then divides and induces abscess formation [7], dependent upon the expression of virulence factors like Gal/GalNAc lectin [20], amoebapore A [21], CP-A5 [22] and the highly positively-charged lysine-and glutamic acid-rich protein KERP1 [23].…”
Section: Pathogenic Process Of E Histolytica European Journal Of Micmentioning
confidence: 99%